The use of technology in an extension course on volleyball: participants' evaluation - Parente, Thomas Augusto [UNESP]; Impolcetto, Fernanda Moreto [UNESP] (State Univ Ceara, Centro Educ Programa Pos-graduacao & Educacao, 2023)
With the aim of evaluate the hybrid extension course named Volleyball, teaching & Sport Pedagogy regarding their structure and organization and their relationship with Information and Comunication Technology, 33 participants who concluded the course answered a questionnaire with closed-ended questions, on a Likert-type scale, and open-ended questions characterizing the study as mixed methodology, on four topics that refer to the use of Information and Comunication Technology throughout the process: a) infrastructure; b) materials; c) assessments; and d) former profile. Most of the analyzed items along the scale received positive and satisfactory ratings, and a very few of those received unsatisfactory ratings, which may indicate that the extension course met the expected proposal. Furthermore, it is understood that hybrid courses, which combine Information and Comunication Technology and practical and presential classes, are a viable possibility for Physical Education further education both for undergraduate students as well as professionals.
Keywords: further education; extension course; Physical Education; Information and Comunication Technology